2009
DOI: 10.2224/sbp.2009.37.3.379
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of transformational leadership with group cohesiveness and emotional intelligence

Abstract: Previous work on transformational leadership has focused predominantly on individual level analysis, while less attention has been paid to investigating why leaders engage in transformational leadership. In this study, group level outcomes pertaining to cohesiveness as well as the antecedent factor of emotional intelligence as it relates to transformational leadership are investigated. Data were collected from 51 department managers and 252 employees in 23 small-medium textile business firms in Taiwan. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 36 publications
(48 reference statements)
2
37
0
2
Order By: Relevance
“…By stimulating intellectually the leader aims to extend their followers" efforts in terms of innovation and creativity (Wang & Huang, 2009). Hence, suggesting alternative problem solutions the transformational leader turns the negative feelings, for instance frustration and helplessness, to more positive and constructive feelings, such as challenge.…”
Section: Dimensions Of Transformational Leadershipmentioning
confidence: 99%
“…By stimulating intellectually the leader aims to extend their followers" efforts in terms of innovation and creativity (Wang & Huang, 2009). Hence, suggesting alternative problem solutions the transformational leader turns the negative feelings, for instance frustration and helplessness, to more positive and constructive feelings, such as challenge.…”
Section: Dimensions Of Transformational Leadershipmentioning
confidence: 99%
“…Only a few studies reviewed in the present studies incorporate multi-rater assessments, such as LDQ, ECI and WLEIS, to provide a more accurate and complete evaluation of an individual's EI competences (Hawkins and Dulewicz, 2007;Wang and Huang, 2009;Barbuto and Wheeler, 2006). The vast dominance of self-reported measures developed for use in exploring the links between leadership and EI may be seen as problematic since socially desirable self and self-knowledge may cause faking goods, which in turn would bring distortion.…”
Section: Discussionmentioning
confidence: 99%
“…The result corroborated the findings of Zhou and George (2003) that emotional intelligence can enhance leadership within team settings. Wang and Huang (2009) found that emotional intelligence and group cohesiveness were positively associated with transformational leadership. The study conducted by George (2000) also showed how the aspects of emotional intelligence -appraisal and expression of emotions, use of emotion to enhance cognitive processing and decision making, knowledge about emotions and management of emotions -contribute to effective employees .…”
Section: Hypotheses Twomentioning
confidence: 98%